2018
DOI: 10.3389/fphar.2018.01438
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclol Attenuates Liver Inflammation Induced by Infection of Hepatitis C Virus via Repressing ROS-Mediated Activation of MAPK/NF-κB Signaling Pathway

Abstract: Treatment with direct-acting antivirals (DAAs) cures most patients infected with hepatitis C virus (HCV) in the real world. However, some patients, especially those with the underlying advanced liver disease, have a limited reduction of liver injury after achieving a sustained viral response (SVR). Bicyclol was widely used in clinics for the treatment of a variety of liver injuries but with an unknown mechanism for the treatment of hepatitis C. We investigated the anti-inflammatory effects and mechanisms of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Bicyclol has been widely used in the clinic to treat patients with chronic HBV infection via interruption of virus replication and improvement of liver function (Zhao and Liu, 2001;Wang and Li, 2006;Liu, 2009). More recently, it was reported that bicyclol effectively suppressed inflammatory response by reversing HCVdisturbed mitochondrial transmembrane potential (Li et al, 2018). Intriguingly, Wang et al also demonstrated that bicyclol exhibited potent anti-proliferative activity in hepatoma cells (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bicyclol has been widely used in the clinic to treat patients with chronic HBV infection via interruption of virus replication and improvement of liver function (Zhao and Liu, 2001;Wang and Li, 2006;Liu, 2009). More recently, it was reported that bicyclol effectively suppressed inflammatory response by reversing HCVdisturbed mitochondrial transmembrane potential (Li et al, 2018). Intriguingly, Wang et al also demonstrated that bicyclol exhibited potent anti-proliferative activity in hepatoma cells (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HCV was likely through upregulation of the glycolipid transfer protein, leading to arrest of viral replication ( 313 ). Furthermore, bicyclol reduced liver inflammation in mice infected by HCV via the suppression of MAPK/NF-κB signaling ( 314 ).…”
Section: Major Aromatic Amino Acid–derived Compounds—the Phenylpropanmentioning
confidence: 99%
“…Natural products were widely reported for the therapy of liver diseases ( Li et al, 2019 ). Bicyclol, a synthetic compound that originated from the Chinese traditional herb Schisandra chinensis , is an approved drug for alleviating liver injuries accompanied by elevated transaminases caused by various etiologies, such as viruses, drugs, alcohol, chemicals, and immunogens ( Liu, 2009 ; Li et al, 2018a ; Li et al, 2018b ). A few studies reported the therapeutic efficacy of bicyclol for NAFLD in clinic ( Li et al, 2020 ) and in animal models ( Zhao et al, 2021 ), though more data are needed to show its clinical benefits and the detailed mechanisms.…”
Section: Introductionmentioning
confidence: 99%